Sebuah Perancangan Brand Identity Oina Craft sebagai Identitas Perusahaan Kriya di Kota Malang - Retnoningtiyas Ningtiyas; Pujiyanto Pujiyanto; Mahendra Wibawa (MAVIS : Jurnal Desain Komunikasi Visual, 2020)
The Oina Craft business is a craft business in the city of Malang which has just been formed and does not yet have an identity to be recognized by the wider community, so it is necessary to design an Oina Craft Brand Identity as the identity of the Craft Company in Malang. The design of the brand identity is carried out using data collection methods such as observation and interviews, then the design method used is through the stages of brainstorming, thumbnail, rough sketch logo, and comprehensive logo, after which a final design is formed which is then tried out on the target audience. The design of the Oina Craft brand identity produces logos as the main and supporting media in the form of logos, Graphic Standards Manual (GSM) books, business cards, letterheads, envelopes, notes, brochures, xbanners, stickers, promotional uniforms, souvenirs, facebook, and Instagram. In conclusion, the media produced certainly have advantages and disadvantages in helping introduce the Oina Craft business.